“ANALYSIS OF FINANCIAL DISTRESS WITH ALTMAN Z-SCORE AND SPRINGATE METHODS AT TEXTILE INDUSTRY LISTED IN INDONESIA STOCK EXCHANGE’’ (International Journal of Psychosocial Rehabilitation, 2020)
Bankruptcy analysis is carried out to obtain an early warning of bankruptcy. The Instrument for analyzing bankruptcy is to use the Altman Z-Score Modification model and the Springate model to predict financial performance, as well as predict the financial position of each company. This study aims to determine whether there are differences in the bankruptcy analysis of the Altman Modified Z-Score model and the Springate model. The results of the Altman and Springate model analysis have unequal variants, seen in the F test with a significance of 0.006 < 0.05. So that conclusions can be drawn, the value of t statistical < t critical (1.00 < 2.306) with a significance of 0.373 > 0.05, then Ho is accepted and Ha is rejected. This means that there is no difference between the Altman Z-Score method with the Springate method in analyzing financial distress in the textile companies from 2008 to 2012.